Water-soluble doubly-strapped isolated perylene diimide chromophore - Yang, Fei (2022)
Perylene diimides (PDIs), a well-studied class of organic dyes, have a strong tendency to self-aggregate in water, thus greatly restricting their phototheranostic applications. Herein, we report a water-soluble PDI cyclophane "Gemini Box" (GBox-14+ ), consisting of a central PDI chromophore enclosed by double-sided cationic molecular straps. Owing to the effective spatial isolation, the chromophore self-aggregation can be completely eliminated, even in a concentrated aqueous solution up to 2 mM. To our knowledge, GBox-14+ represents an interesting example of a fluorescent PDI cyclophane in water, capable of being employed for lysosome-targetable live-cell imaging. More importantly, the highly concentrated aqueous solution of PDI radical anion can be significantly stabilized by GBox-14+ to exhibit an excellent near-infrared photothermal effect, which was further exploited for efficient and selective antibacterial applications. This work provides a new access to water-soluble non-aggregated organic dyes and promotes their potential biomedical applications.